KEMAMPUAN BERBICARA SISWA DALAM MENANGGAPI CARA PEMBACAAN CERPEN KELAS VIIA DAN VIIB SMPN 19 MUARA FAJAR PEKANBARU TAHUN AJARAN 2013/2014: (The Students’ Ability to Speak in Response to Reading Short Stories VIIA Muara Fajar Pekanbaru Academic Year 2013/2014 ) - Supriyadi Supriyadi; Reniwati Reniwati; Tri Yuliawan (Perspektif Pendidikan dan Keguruan, 2016)
Indonesian has important and strategic role in the communication process in the middle ofthe association and social interaction. Through the Indonesian language is good and true,someone will be able to communicate both verbally and in writing to the other party inaccordance with the context and situation. Their speaking ability is good enough for theirspeaking style was influenced by the dialect of the native language. So the aim of this studywas to determine the students' ability to speak in response to the reading of short storiesseventh grade students of SMPN 19 Muara Fajar. The issues raised in this research is: how isthe ability to speak the seventh grade students of SMPN 19 Muara Fajar in response to theway short story readings on aspects of pronunciation and intonation ?, how is the student'sability SMPN 19 Muara Fajar in response to a short story readings on suitability aspects oflanguage? How the ability of students of class VII SMPN 19 Muara Fajar in response to ashort story readings on aspects of mime and expression ?. The theory used is the theory Tarin,Nurgiantoro, Bungin, Sudjono, Suharma, Tri Endah Priyatni and Mustafa.populasi 147people with a sample of 70 students selected at random. The method which the researchersused was descriptive quantitative method. To collect data the researchers using observationand oral test. The conclusion of this study are: speech class VII SMPN 19 Muara Fajar inresponse to the reading of short stories academic year 2013/2014 on aspects of pronunciationcategorized either with an average value of 77. The ability to speak the seventh gradestudents of SMPN 19 Muara Fajar in response to a short story readings on aspects suitabilityenough language category with an average of 62. the ability to speak the seventh gradestudents of SMPN 19 Muara Fajar in response to a short story readings on aspects of goodgestures and expressions category with an average of 73.